Mother's Knowledge Levels on Baby Massage for 0-12 Months Old Babies at PMB Ni Kadek Kurniati, A.Md., Pemogan South Denpasar - Made Pradnyawati Chania; Kadek Lisanita Dewi Swantari; Ni Wayan Sukma Adnyani (WMJ (Warmadewa Medical Journal), 2024)
Baby massage is a tactile stimulation on the surface of the baby's skin. In order to increase the baby's growth and development optimally, performing the baby massage activities needs good knowledge of the mother. The purpose of this study was to describe the level of knowledge of mothers about infant massage aged 0-12 months at private midwive practice Ni Kadek Kurniati, A.Md.Keb Pemogan, South Denpasar. This study used a descriptive method with a cross sectional design. The samples were 30 mothers who had babies aged 0-12 months who met the inclusion criteria. Primary data retrieval using a questionnaire. The results obtained were; most of the respondets are aged 20-35 years, have a high school education level and have of the sources of information obtained through health workers (83.33%; 60%, and 36.67%, respectively). Most mothers who have good knowledge were in the age range of 20-35, have a high school education level, and obtain knowledge from health workers (88%; 88.89%, and 100%, respectively). In conclusion, almost all respondents have good knowledge about baby massage. It is expected that mothers who have babies aged 0-12 months to further increase their knowledge so that they can apply the practice of baby massage at home independently and for health workers to better educate the public and strengthen counseling, training and information dissemination, especially through social media so that the information provided becomes appropriate. and right on target.